Social avoidance and social adjustment in Chinese preschool migrant children: the moderating role of teacher–child relationships - Zhu, Jingjing; Yin, Xiaoqi; Li, Xiaoyun; Dong, Xinyi; Zou, Shiyao; Li, Yan (Frontiers in Psychiatry, 2023)
Objectives This study aimed to explore the moderating role of teacher–child relationships in the relations between social avoidance and social adjustment (i.e., prosocial behavior, peer exclusion, and anxious-fearful behavior) in Chinese migrant preschoolers. Methods Participants were 148 migrant children aged 4–6 years (82 boys, Mage = 62.32, SD = 6.67) attending kindergartens in Shanghai, People's Republic of China. Mothers reported children's social avoidance, and teachers rated teacher–child relationships and children's social adjustment. Results Results indicated that social avoidance was positively related to peer exclusion and negatively related to prosocial behavior. Teacher–child relationships moderated those associations. Specifically, teacher–child closeness buffered the relationship between social avoidance and peer exclusion, whereas teacher–child conflict exacerbated the relations between social avoidance and peer exclusion and anxious-fearful behavior. Conclusion The current finding informs us of the importance of improving teacher–child closeness and reducing teacher–child conflict to buffer the negative adjustment among socially avoidant young children who migrated from rural-to-urban China. The findings also highlight the importance of considering the meaning and implication of social avoidance for migrant preschoolers in Chinese culture.